Antibiotic prophylaxis for childbirth-related perineal trauma: A systematic review and meta-analysis - Hannah Armstrong; Jane Whitehurst; R. Katie Morris; Victoria Hodgetts Morton; Rebecca Man (PLoS ONE, 2025)
Introduction Childbirth-related perineal trauma affects the vast majority of women who give birth vaginally and subsequent complications such as wound infection occur frequently. Antibiotic prophylaxis is not currently recommended following first or second degree tears, or episiotomies. We aimed to evaluate the effectiveness of prophylactic antibiotics for preventing complications from perineal trauma across all types of childbirth-related perineal trauma. Materials and methods Databases were searched from inception to February 2024. Randomised controlled trials, non-randomised interventional studies and observational studies were eligible for inclusion where women experienced childbirth-related perineal trauma and received antibiotic prophylaxis or placebo, including any type of tear or episiotomy. The primary outcome was perineal wound infection. Results were combined into meta-analysis using a random effects model. Results 14 studies were eligible for inclusion (eight randomised controlled trials, six observational) involving 8,878 women. Ten studies were deemed to have a high overall risk of bias. Overall the GRADE certainty of findings were low. Twelve studies were included in the analysis for perineal wound infection, involving 8,438 women. There was a reduced rate of perineal wound infection when prophylactic antibiotics were received (relative risk 0.57, 95% confidence interval 0.48 to 0.67). The subgroup analysis by type of tear demonstrated association with reduced risk of infection when prophylactic antibiotics were received, in the non-obstetric anal sphincter injuries combined subgroup (relative risk 0.50, 95% confidence interval 0.41–0.63) and the episiotomy only subgroup (relative risk 0.57, 95% confidence interval 0.36–0.91). Conclusions Prophylactic antibiotics are associated with a reduced risk of perineal wound infection. Despite these findings, there are not sufficient high-quality randomised controlled trials to adequately inform guideline change amongst women with first/second degree tears or episiotomies. We recommend that an adequately powered, robust, randomised controlled trial is needed amongst women with first/second degree tears or episiotomies after spontaneous birth.